2020
DOI: 10.1186/s13098-020-0517-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors for carotid intima-media thickness in patients with type 2 diabetes mellitus in Western China assessed by logistic regression combined with a decision tree model

Abstract: Background: Cardiovascular disease (CVD) is the leading cause of morbidity and mortality in patients with type 2 diabetes (T2DM). Carotid intima-media thickness (CIMT) is considered a preclinical stage of atherosclerosis. Therefore, it is necessary to identify the related risk factors for CIMT to facilitate the early prevention of CVD. Previous studies have shown that visceral fat area (VFA) is a risk factor for T2DM and CVD. However, few studies have focused on the effects of VFA on CIMT associated with T2DM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 71 publications
1
15
1
4
Order By: Relevance
“…To evaluate the difference in ccIMT change (mean and max, respectively) between the two groups a one-way analysis of covariance (ANCOVA) was used, using the baseline ccIMT values (mean and max, respectively) as covariates (33,34). The ANCOVA analyses were then repeated adjusting for several confounders gained from the literature [35][36][37][38] and from associations observed in this study population. Apart from baseline mean or max ccIMT, the covariates adjusted for were sex, age, smoker status, body mass index (BMI), total cholesterol, LDL cholesterol, HDL cholesterol, systolic and diastolic blood pressure, and HbA1c.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…To evaluate the difference in ccIMT change (mean and max, respectively) between the two groups a one-way analysis of covariance (ANCOVA) was used, using the baseline ccIMT values (mean and max, respectively) as covariates (33,34). The ANCOVA analyses were then repeated adjusting for several confounders gained from the literature [35][36][37][38] and from associations observed in this study population. Apart from baseline mean or max ccIMT, the covariates adjusted for were sex, age, smoker status, body mass index (BMI), total cholesterol, LDL cholesterol, HDL cholesterol, systolic and diastolic blood pressure, and HbA1c.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A decision-tree algorithm is a data-mining technique that reveals a series of classification rules by identifying priorities. It has been used to identify the profiles associated with the progression of chronic kidney disease [ 55 ]. The decision-tree analysis showed that age was the initial classifier for the ADV/TDF-related renal tubular dysfunction.…”
Section: Clinical Profile For the Adv/tdf-related Renal Tubular Dymentioning
confidence: 99%
“…Представлены только факторы, продемонстрировавшие статистическую значимость. [46][47][48]. ТКИМ является одним из маркеров раннего сосудистого старения и часто используется в крупных исследованиях, включая генетические, как маркер раннего атеросклероза в связи с относительной простотой, доступностью и неинвазивностью методики измерения [49].…”
Section: результаты и обсуждениеunclassified